Bacterial preys and commensals condition the effects of bacteriovorus nematodes on Zea mays and Arabidopsis thaliana - Matus-Acuña, Violeta; Caballero-Flores, Gustavo; Reyes Hernández, Blanca Jazmín; Martínez-Romero, Esperanza (Applied soil ecology, 2018)
In this study, we analyzed the nematode-bacteria-plant interaction by using bacteriovorus nematodes isolated from maize rhizosphere and plant growth promoting rhizobacteria to evaluate their effect on plant growth and root development of maize and Arabidopsis thaliana. Two bacterial feeding nematodes, identified as Oscheius tipulae and Mesorhabditis sp., displayed distinct attraction patterns for seven rhizosphere bacteria with a strong bias towards Rhizobium strains. We tested the effect of these two nematodes on both plant growth and root morphology using native Zea mays and found that the co-inoculation of Rhizobium phaseoli Ch24-10, a plant growth promoter, and maize rhizosphere nematodes, increased dry weight of corn plants compared to plants treated only with bacteria or the nematode. Additionally, we found that the nematodes reduced the weight and length of the primary root and increased the number of emerging lateral roots. We further analyzed the effect of nematodes and bacteria using the model plant A. thaliana and observed similar effects on roots as those found in native corn. Nematodes reduced the primary root growth and increased the number of emerging lateral roots. The model nematode Caenorhabditis elegans N2 alone had no effect on A. thaliana plants, it became capable of affecting root morphology when fed with Acinetobacter pittii, which was originally isolated from the maize rhizosphere nematodes. Our results suggest a synergistic effect of nematodes and their associated bacteria both in plant development and root morphology, highlighting the importance of nematode-bacteria interactions in shaping plant growth and root morphology. A model of nematodes as Trojan horses carrying bacteria is proposed.